Pembaharuan Pendidikan Islam (Studi Pemikiran Muhammad Abduh Dan Rasyid Ridha) - ayu ningsih; Kholid Mawardi; Rohmat Rohmat (Jurnal Penelitian Agama, 2021)
This article tries to discuss the renewal education of Islam in the midst of western modernization by taking the thoughts of Muhammad Abduh and Sayyid Muhammad Rasyid Ridha. Muhammad Abduh and Rasyid Ridha's Islamic renewal education thought was influenced by the thoughts of their teachers. Muhammad Abduh and Rasyid Ridha believe that Islam encompasses political aspect, social aspect and spiritual aspect. In order to arouse these attitudes, Muslims must return to the teachings of Islam taught by the Prophet Muhmmad SAW and his companions. The presence of Muhammad Abduh and Rasyid Ridha as Islamic reformers aims to revive the spirit of the Muslim struggle against colonialism, so that Muslims are free from colonialism in the western world. The spirit of the Islamic community competed with advances in science, technology and the development of times in other fields is expected to increase through their thoughts. The result of this article show that Muhammad Abduh and Rasyid Ridha contribute in the form of thoughts on the renewal of Islamic education in the field of curriculum and institutions